5‐Hydroxymethylcytosine is a nuclear biomarker to assess biological potential in histologically ambiguous heavily pigmented melanocytic neoplasms. (6th February 2017) - Lee, Jonathan J.; Vilain, Ricardo E.; Granter, Scott R.; Hu, Nina R.; Bresler, Scott C.; Xu, Shuyun; Frank, Alexander H.; Mihm, Martin C.; Saw, Robyn P.M.; Fletcher, Christopher D.; Scolyer, Richard A.; Murphy, George F.; et al.
Abstract : Background: 5‐Hydroxymethylcytosine (5‐hmC) is an epigenetic marker detectable through immunohistochemistry (IHC) that has been shown to distinguish benign nevi from melanoma with high sensitivity and specificity. The purpose of the study was to explore its diagnostic utility in a subset of histologically challenging, heavily pigmented cutaneous melanocytic neoplasms. Methods: 5‐hmC IHC was performed on 54 heavily pigmented melanocytic tumors. Semi‐quantitative analysis of immunoreactivity was correlated with clinical, pathologic and follow‐up data. Results: Benign melanocytic neoplasms (4 of 4 blue nevi with epithelioid change; 12 of 12 combined nevi; 5 of 5 deep penetrating nevi, DPN) exhibited strong 5‐hmC nuclear reactivity. Eight heavily pigmented blue nevus‐like melanomas and 7 of 8 pigmented epithelioid melanocytomas (PEM) showed significant 5‐hmC loss. Five of 7 atypical DPN cases and 8 of 10 melanocytic tumors of uncertain malignant potential (MELTUMP) showed low to intermediate 5‐hmC immunoreactivity. These differences were statistically significant ( P ‐value <.0001). Conclusions: Loss of 5‐hmC may be helpful in differentiating benign, diagnostically challenging, heavily pigmented melanocytic tumors from those with malignant potential. The intermediate to low 5‐hmC immunoreactivity in atypical DPNs, PEMs and so‐called MELTUMP categories further underscores the need to consider these neoplasms as having some potential for lethal biological behavior.